Elastic scattering of 16O on 12C in the framework of two-center model; Physics Letters B; Vol. 55, iss. 2 (3 Febr.) - Cherdantsev P. A. Piotr Alekseevich (1975, 1975)
The model for the description experimentally observed intermediate structure and the sharp backward rise of the cross sections of elastic 12C + 16O scattering is proposed. The deformation and interior structure of the colliding nuclei are taken into account. The qualitative agreements for elastic scattering cross sections are obtained.